PRINCIPLES OF INSTRUCTIONAL VIDEO USED IN TEACHER’S VIDEO BASED LEARNING TO TEACH ENGLISH - Vinda Yulia Agustin; Muhammad Saifuddin (Universitas Pesantren Tinggi Darul Ulum Jombang (Unipdu), 2022)
This objective of this research was to figure out the principles of instructional video applied by the teacher to present the English material English and to explain the relevance of provided material in the video to the principles of instructional video. To answer the research questions, qualitative research design was used. The data were teaching materials as the content of the video which represented the principles of English teaching material used in video based learning. The finding of the research showed that the teacher applied 3 principles of instructional design, the theory used was from Carliner’s (2000). There were 3 principles used physical design, cognitive design and affective design. The content of the video covering physical design, cognitive design and affective design were relevantly used based on the principles of instructional videos. In conclusion, based on the analysis of the identified data, the video was relevantly design presenting the principles of instructional video based on Carlinger’s theory.